2020
DOI: 10.20452/pamw.15635
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is more frequently associated with non-obstructive coronary lesions: The Bialystok Coronary Project

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Overall, coronary angiography is the most effective method used to evaluate coronary vessels, especially in patients with acute coronary syndrome. In one of our previous studies, we observed that a substantial number of patients with atrial fibrillation show no significant narrowing of coronary arteries during coronarography [ 50 ]. In the present analysis, 62.49% of patients with AF presented with non-obstructive coronary lesions on angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, coronary angiography is the most effective method used to evaluate coronary vessels, especially in patients with acute coronary syndrome. In one of our previous studies, we observed that a substantial number of patients with atrial fibrillation show no significant narrowing of coronary arteries during coronarography [ 50 ]. In the present analysis, 62.49% of patients with AF presented with non-obstructive coronary lesions on angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the findings were based on a small population and were obtained from a retrospective single-centre study, a multi-centre prospective study should be conducted to verify these results. 5 As mentioned above, coronary angioplasty was less common in patients with AF compared to those with sinus rhythm. This raises the possibility that it may be difficult to discover patients with AF for invasive procedures.…”
Section: Future Directionsmentioning
confidence: 93%
“…4 However, other studies have reported that the independent association of the absence of AF with the localization of significant coronary lesions indicates a mixed (coronary and non-coronary) AF origin in patients with coronary artery disease (CAD). 5 Therefore, whether atrial coronary circulation plays an important role in the formation of AF is unknown. Further investigation is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical risk factors promoting the development of AF were identified, such as older age, male sex, obesity, hypertension, coronary artery disease, heart failure (HF), chronic kidney disease, hyperthyroidism, diabetes mellitus (DM), chronic obstructive pulmonary disease (COPD) and valvular heart disease [ 23 , 24 , 25 ]. These disorders are responsible for the induction of unfavorable atrial structural remodeling and formation of the morphological substrate sustaining the arrhythmia.…”
Section: General Mechanisms Of Afmentioning
confidence: 99%